Priming of conflicting motivational orientations in heavy drinkers: robust effects on self-report but not implicit measures - Di Lemma, Lisa C. G.; Dickson, Joanne M.; Jedras, Pawel; Roefs, Anne; Field, Matt (Frontiers in Psychology, 2015)
We report results from three experimental studies that investigated the independence of approach and avoidance motivational orientations for alcohol, both of which operate within controlled and automatic cognitive processes. In order to prime their approach or avoidance motivational orientations, participants watched brief videos, the content of which (positive or negative depictions of alcohol, or neutral) varied by experimental group. Immediately after watching the videos, participants completed self-report (Approach and Avoidance of Alcohol Questionnaire; all studies) and implicit (visual probe task in study 1, stimulus-response compatibility task in studies 2 and 3) measures of alcohol-related approach and avoidance. In study 3, we incorporated an additional experimental manipulation of thought suppression in an attempt to maximize the influence of the videos on implicit measures. Findings were consistent across all three studies: increases in self-reported approach inclinations were mirrored by decreases in avoidance inclinations, and vice versa. However, a combined analysis of data from all studies demonstrated that changes in approach inclinations were partially independent of changes in avoidance inclinations. There were no effects on implicit alcohol-related processing biases, although methodological issues may partially account for these findings. Our findings demonstrate that subjective approach and avoidance inclinations for alcohol tend to fluctuate in parallel, but changes in approach inclinations may be partially independent from changes in avoidance inclinations. We discuss methodological issues that may partially account for our findings.